2016
DOI: 10.1016/j.foodchem.2015.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated lipid matrices protect plant sterols from degradation during heating treatment

Abstract: The interest in plant sterols enriched foods has recently enhanced due to their healthy properties. The influence of the unsaturation degree of different fatty acids methyl esters (FAME: stearate, oleate, linoletate and linolenate) on a mixture of three plant sterols (PS:campesterol, stigmasterol and β-sitosterol) was evaluated at 180 °C for up to 180 min.Sterols degraded slower in the presence of unsaturated FAME. Both PS and FAME degradation fit a first order kinetic model (R 2 >0.9). Maximum oxysterols conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Both the presence of an acyl moiety in the cholesteryl ester and its unsaturation affected the rate of cholesteryl molecule oxidation [30]. It has been shown that the presence of unsaturated fatty acids in a heated medium hindered phytosterol degradation [27]. Similar degradation levels to those found in our results were observed when stigmasterol was heated for 2 h at 180 °C in sunflower oil [31].…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Both the presence of an acyl moiety in the cholesteryl ester and its unsaturation affected the rate of cholesteryl molecule oxidation [30]. It has been shown that the presence of unsaturated fatty acids in a heated medium hindered phytosterol degradation [27]. Similar degradation levels to those found in our results were observed when stigmasterol was heated for 2 h at 180 °C in sunflower oil [31].…”
Section: Resultssupporting
confidence: 84%
“…When the influence of the degree of unsaturation of different lipid matrices (methyl esters of stearic, oleic, linoleic and linolenic acids) on a mixture of three plant sterols (campesterol, sitosterol and stigmasterol) at 180 °C for up to 3 h was performed, the kinetic constant value progressively decreased along with the degree of unsaturation [27]. Greater levels of unsaturation of the lipid matrix exhibited a protective effect against the degradation of plant sterols during heating, indicating that degradation of unsaturated fatty acids was easier than sterols [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies show that sterols degrade slower in the presence of unsaturated fatty acids. Nevertheless, in a recent review, it has been mentioned that “the behavior of phytosterols under different degree of unsaturation of the surrounding lipids needs further investigation.” It was suggested that oxidation of unsaturated phytosterols may protect other compounds from their oxidation . Β‐sitosterol was found to have in vitro capacity to trap free radicals …”
Section: Introductionmentioning
confidence: 99%